Perception of non-communicable diseases predicts consumption of fruits and vegetables - Charles Surjadi; Ismoyowati Ismoyowati; Dwidjo Susilo; Hernani Djarir (Universa Medicina, 2012)
BackgroundNutrition has come to the fore as one of the major modifiable determinants of chronic disease. Establishing healthy eating habits during adolescence is important given that fruit and vegetable consumption has long-term health-protective benefits. The objective of this study was to investigate the determinant factors of fruit and vegetable consumption habits among Padang inhabitants MethodsWe conducted a questionnaire-based rapid assessment of 150 respondents who came from different settings: The questionnaire consisted of items on personal characteristics such as age, working status, gender, and personal knowledge of the subjects about the cause of non-communicable diseases (NCDs) and their activities to prevent NCDs. Bivariate analysis was applied to look for variables significantly related to healthy eating (vegetable and fruit consumption). We applied multiple logistic regression to look for the best model to explain factors related to regular fruit and vegetable consumption.Results The age range of the subjects was 14 to 76 years, 60% of subjects were women, and 40% were men. The study indicated that 64.7% of the respondents perceived that eating habits relate to NCD, while 67.3% consumed fruits and vegetables regularly. Multivariate logistic regression analysis indicated that gender (O.R.=2.74; 95% C.I. 1.54-5.27) and perception of NCD as being related to healthy eating (O.R.=5.62;95% C.I. 2.93-10.76) were significantly related to regular fruit and vegetable consumption. ConclusionThis study demonstrated that perception of NCD was the most determinant factor of regular fruit and vegetable consumption. Activities to improve practice of regular fruit and vegetable consumption are part of control of NCD risk factors.